Bonuses and performance evaluations - Dirk Sliwka (IZA World of Labor, 2020)
Economists have for a long time argued that performance-based bonuses raise performance. Indeed, many firms use bonuses tied to individual performance to motivate their employees. However, there has been heated debate among human resources professionals recently, and some firms have moved away from individual performance bonuses toward fixed wages only or collective performance incentive schemes such as profit-sharing or team incentives. The appropriate approach depends on each company's unique situation, and managers need to realize that individual bonus plans are not a panacea to motivate employees.
Keywords: M5; M52; J33; 330; bonus; compensation; variable pay; incentives; performance evaluation; evidence-based bonus design